2001
DOI: 10.1051/0004-6361:20010459
|View full text |Cite
|
Sign up to set email alerts
|

An active binary XY UMa revisited

Abstract: Abstract. New extensive multicolour photoelectric photometry, performed since 1994, is presented. 17 moreor-less complete light curves were obtained and analyzed. The Wilson-Devinney code applied to the BVRI light curves without the maculation effect together with published spectroscopic mass ratio and semi-major axis yielded new absolute parameters of the eclipsing pair: m1 = 1.10 M , m2 = 0.66 M , R1 = 1.16 R , R2 = 0.63 R , a = 3.107 R and the orbital inclination i = 80.9• . The observed orbital period chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 33 publications
0
37
1
2
Order By: Relevance
“…They revealed that two component stars in the close binaries are magnetic connecting, and the active longitude belts are related to the interaction between magnetic fields. Pribulla et al (2000) found starspots on both stars of the short-period RS CVn-type binary RT And were facing to each other. They inferred that there was a magnetic bridge connecting two active regions on the component stars, which may lead to a mass transfer between two stars.…”
Section: Discussionmentioning
confidence: 94%
“…They revealed that two component stars in the close binaries are magnetic connecting, and the active longitude belts are related to the interaction between magnetic fields. Pribulla et al (2000) found starspots on both stars of the short-period RS CVn-type binary RT And were facing to each other. They inferred that there was a magnetic bridge connecting two active regions on the component stars, which may lead to a mass transfer between two stars.…”
Section: Discussionmentioning
confidence: 94%
“…The photometric variability of XY UMa was first noted by Geyer et al ( 1955). The binary has been the subject of extensive photometric studies; for references see Pribulla et al ( 2001). The spectroscopic orbit of the primary component was first obtained by the cross-correlation function technique by Rainger et al (1991).…”
Section: Xy Umamentioning
confidence: 99%
“…From the short timescale observations (LC9 and LC10) by Macuso et al (1979a) and from the October observations and the December observations (LC17 and LC18) by Dapergolas et al (1991) and Gordon et al (1990), respectively (see Pribulla et al 2000) there was no similar rule for other parameters of the same spot (spot area, latitude, and temperature). For the other short-period RS CVn system XY UMa, Pribulla et al (2001) identified the same spots on the subsequent LCs. From their results, we conclude that the area and temperature of the same spot change very little over a short time interval, one month or so, on condition that the spot latitude is fixed.…”
Section: Analysis Of the Light Curve In 2005 And 1999mentioning
confidence: 63%
“…Heckert et al (1998) find that WY Can had secular variations during the secondary eclipse, but it was not explained by a spot model. For another short-period RS CVn system, XY UMa, Pribulla et al (2001) find that the LCs 8 and 9 in 1999 showed equal maxima and the deep secondary minimum, and this behavior was explained by putting a large cool starspot on the primary facing the observer at the secondary minimum.…”
Section: Analysis Of the Light Curve In 2005 And 1999mentioning
confidence: 93%